SINGLE-THREAD CHAIN STITCH TYPE 101 SEWING MACHINES - MANOILENKO, OLEKSANDR; BEZUHLYI, DMYTRO; HOROBETS, VASYL; BURMISTENKOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper investigates the thread take-up mechanism of typical sewing machines used to form single-thread chain stitches of type 101. The nature of the actual thread feed function for an ideal thread and its correspondence to the required feed is analyzed. The study focuses on the geometric and kinematic characteristics of the thread take-up mechanism, without considering the influence of the main shaft rotation frequency or thread tension; the thread is assumed to be ideal in the calculations. The results show that these machines demonstrate excessive thread feeding (deviations of 6.2–64.4%), which leads to a significant oversupply compared to the required parameters (e.g., 53.3 mm versus the required ≈32 mm under minimal stitch conditions). The absence of a mechanism for adjusting the actual thread feed function results in an uneven stitch structure when sewing materials of varying thicknesses and stitch lengths. This negatively affects the final physical and mechanical properties of the thread connection or reinforcement in 3D textile framework products. The obtained data confirm the sufficient accuracy of the analytical model (with deviations not exceeding ±2%) and can be used for the improvement or development of a thread take-up mechanism with adjustable feed function. The nature of the feed function allows the stitch formation process of type 101 to be assessed in the first approximation and provides an objective evaluation of stitch quality. The derived analytical dependencies can be applied in further studies, taking into account the real physical and mechanical properties of different threads, and in the development or enhancement of mechanisms to improve the stitch formation process.